1999
DOI: 10.1097/00002508-199909000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender and Acute Dental Pain on Thermal Pain Responses

Abstract: These data suggest that the sex difference in thermal pain sensitivity frequently reported in pain-free subjects appears to be absent in patients presenting with acute dental pain. However, this effect cannot be explained solely based on the presence of clinical pain because the effect on pain threshold and tolerance persisted into session 2, when pulpitis patients were pain free. Potential explanations for these results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Forty-six dental patients experiencing pain due to acute irreversible pulpitis and 33 healthy controls were involved in a study 7 to determine whether the presence of pain could be infl uenced by gender. These data suggest that the gender difference in thermal pain sensitivity frequently reported in pain-free subjects appears to be absent in patients presenting with acute dental pain.…”
Section: N B R I E Fmentioning
confidence: 99%
“…Forty-six dental patients experiencing pain due to acute irreversible pulpitis and 33 healthy controls were involved in a study 7 to determine whether the presence of pain could be infl uenced by gender. These data suggest that the gender difference in thermal pain sensitivity frequently reported in pain-free subjects appears to be absent in patients presenting with acute dental pain.…”
Section: N B R I E Fmentioning
confidence: 99%
“…Additional t tests and 2 analyses indicated no other sex differences for any demographic or clinical variables (data not presented), which is consistent with previous clinical investigations. 13,20,42,66 Bivariate Relationships…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…We have previously reported on gender differences in thermal pain responses in this sample. 4 All subjects provided informed consent for the study, and all procedures were approved by the University's Institutional Review Board.…”
Section: Subjectsmentioning
confidence: 99%
“…4 Briefly, the earlier study demonstrated that the sex differences in thermal pain responses frequently observed in pain-free subjects 25 were not observed in patients with acute dental pain. Thermal pain responses and catastrophizing were assessed in patients with acute dental pain at 2 time points, before and after successful pain-relieving treatment.…”
mentioning
confidence: 99%